2000
DOI: 10.1038/sj.bjp.0703084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of 17 β‐oestradiol induced vasodilatation in isolated pressurized rat small arteries

Abstract: 1 The in¯uence of 17 b-oestradiol on pressurized isolated rat mesenteric and coronary small arteries was investigated. 2 17 b-oestradiol caused rapid (t 1.0 55 mins) concentration-dependent relaxations of pre-contracted pressurized (50 mmHg) isolated rat mesenteric and coronary arteries. Similar responses were observed in both vessel types. Signi®cant relaxations were only observed at concentrations exceeding 3 mM. 3 The vasodilatory responses in both types of artery were una ected by 10 mM L-nitro arginine (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 69 publications
5
58
0
Order By: Relevance
“…Although there are numerous reports in the literature detailing the beneficial influence of estrogen replacement on the vasculature in young animals (4,10,14,41), to our knowledge this is the first study to examine the effects of estrogen supplementation on the coronary vasculature in female rats of an advanced age. The foremost finding of this study is that age reduces flow-induced, NO-mediated vasodilation of coronary arterioles of female rats, and estrogen replacement improves flow-induced dilation in coronary arterioles of old female rats, indicating a favorable coronary endothelial response to estrogen replacement in this aged population.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous reports in the literature detailing the beneficial influence of estrogen replacement on the vasculature in young animals (4,10,14,41), to our knowledge this is the first study to examine the effects of estrogen supplementation on the coronary vasculature in female rats of an advanced age. The foremost finding of this study is that age reduces flow-induced, NO-mediated vasodilation of coronary arterioles of female rats, and estrogen replacement improves flow-induced dilation in coronary arterioles of old female rats, indicating a favorable coronary endothelial response to estrogen replacement in this aged population.…”
Section: Discussionmentioning
confidence: 99%
“…Like the body of experimental information regarding NO-related mechanisms, the results of some studies support a role for vasodilator prostanoids in the acute actions of estrogen (29,30), while others do not (25,27,31). Of some additional interest, many of the studies on peripheral vascular tissue, reporting prostanoid-and/ or NO-dependence, also found that the acute E2 response could be blocked by pretreatment with an estrogen receptor blocker (7, 14, 17 -19, 22).…”
Section: Estrogen and Vasodilationmentioning
confidence: 94%
“…Evidence for direct actions of estrogen on non-cerebral vascular smooth muscle has been obtained in isolated cell systems and in endotheliumdenuded vessel preparations. Some reports have revealed a stereoselective effect of estrogen (9,27,32) on vascular smooth muscle that may (9,32) or may not (25,27,33) involve classical estrogen receptors. Other publications point to direct vascular smooth muscle relaxant effects of estrogen that variously depend upon: a) increases in intracellular cAMP (9,26) or cGMP (26); b) activation of the cGMP-dependent kinase (34); c) potentiation of Ca…”
Section: Estrogen and Vasodilationmentioning
confidence: 99%
“…Estrogen receptors have been identified on both vascular endothelial (4,10) and smooth muscle cells (5,21,22,29), providing two potential pathways by which estrogen could affect vascular function. In addition, non-receptor-mediated mechanisms may play a role (35). Estrogen treatment has been reported to increase production of the vasodilator nitric oxide (8) but to decrease production of the inducible nitric oxide synthetase (38).…”
mentioning
confidence: 99%